Stereoselective synthesis of E-3-(arylmethylidene)-5-(alkyl/aryl)-2(3H)-furanones by sequential hydroacyloxylation-Mizoroki–Heck reactions of iodoalkynes. Issue 42 (16th October 2018) - Muthusamy, Gopinathan; Pansare, Sunil V.
Abstract : Stereoselective hydroacyloxylation of iodoalkynes with β-aryl cinnamic acids and subsequent Mizoroki–Heck reaction provides an efficient route to substituted 2(3 H )-furanones. Abstract : A modular, stereoselective synthesis of E -3-(arylidene)-5-(alkyl/aryl)-2(3 H )-furanones was developed. The methodology features regioselective addition of β-aryl acrylic acids to iodoacetylenes to furnish the Z -acyloxy iodoalkenes. A stereoselective 5- exo-trig Mizoroki–Heck reaction of the acyloxy iodoalkenes generates the target E -2(3 H )-furanones. The approach was applied in a formal synthesis of the naturally occurring kinase inhibitor BE-23372M.